Detection of Swine Influenza A and Porcine Reproductive and Respiratory Syndrome Viruses in Nasopharynx-Associated Lymphoid Tissue. (September 2022) - Niazi, Ahmad M.; ZiHeng, Zhou; Fuke, Naoyuki; Toyama, Keiko; Habibi, Wazir A; Kawaguchi, Nijiho; Yamaguchi, Ryoji; Hirai, Takuya
Summary: Porcine respiratory disease complex, which is caused by a combination of pathogens, including swine influenza A virus (SIV) and porcine reproductive respiratory syndrome virus (PRRSV), results in significant economic losses in pig production systems. Nasopharynx-associated lymphoid tissue (NALT) plays an important role in the uptake of pathogens and defence of the nasal mucosa in rodents and humans. We characterized NALT M cells in pigs and detected SIV antigen and PRRSV nucleic acid in NALT using histopathological, immunohistochemical and in-situ hybridization analyses. All SIV- and PRRSV-positive cases examined had suppurative nasopharyngitis and pneumonia. M cells were detected by immunohistochemistry and the distribution of M cells showed an increase in the middle section of NALT. SIV antigen was detected in M cells and PRRSV nucleic acid was demonstrated in the cytoplasm of macrophages in NALT. We believe that SIV and PRRSV infection in the upper respiratory tract induces local immunosuppression and these results confirm that swine NALT is a location for virus replication and may be strongly associated with the development of pneumonia in pigs. Graphical abstract: Image 1